Impact of the local community protest on the decision on environmental conditions - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2019)
The paper aims to determine the significance and legal effects of a local community protest expressed as part of public participation in an individual environmental impact assessment. More specifically, it is to determine the impact of such a protest on the decision on environmental conditions, and in particular whether the protest may constitute a basis for refusing to issue such a decision. In the conclusions, the author indicates that the protest expressed as part of the public participation in the proceedings concerning the issuance of a decision on environmental conditions cannot constitute a sufficient basis for a negative decision. Based on the rational planning model, it is also argued that the concept of public participation in environmental proceedings as defined by law is still deeply rooted in the rational model of environmental impact assessments. As a consequence, it determines the actual limits of public participation in these matters.